Large-scale cryogenic gravitational-wave telescope in Japan: KAGRA. (April 2015) - Akutsu, Tomotada
Abstract: KAGRA, the large-scale cryogenic gravitational-wave telescope (formerly known as LCGT), is a laser interferometric detector under construction at the Kamioka mine in Japan. We report on the current status of the project as well as the overview of the main features and the schedule. The construction has been underway since 2012, and the tunnel excavation in the mine for two 3-km arms finished at the end of March 2014. As with the other advanced terrestrial interferometers, KAGRA will have two long Fabry-Perot cavities to sense gravitational waves, but they are to be installed underground for lower seismic noise. KAGRA will be the first large interferometer having cryogenic cavities, the mirrors for which are planned to be cooled down to around 20 K for reducing thermal noise.